2018
DOI: 10.1007/s00330-017-5203-3
|View full text |Cite
|
Sign up to set email alerts
|

Does patient age affect the PPV3 of ACR BI-RADS Ultrasound categories 4 and 5 in the diagnostic setting?

Abstract: • In patients with category 4 lesions , the likelihood of malignancy is associated with age. • In patients with category 5 lesions, the association is not definite. • Closer attention should be given to older patients in applying the ACR BI-RADS US.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…It can be highly specific in the identification of metastases (12). Although our data indicated that the rate of lymph node metastasis gradually increased as the BI-RADS US category steadily increased, 12.3% (9/73) of patients with a category 4A malignant lesion also presented a positive axillary status (8). In this study, the US lymph node status had the most important contribution in predicting malignancy in the nomogram, followed by suspicious calcifications on MG. Other MG features did not show distinct predictive value in this study.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…It can be highly specific in the identification of metastases (12). Although our data indicated that the rate of lymph node metastasis gradually increased as the BI-RADS US category steadily increased, 12.3% (9/73) of patients with a category 4A malignant lesion also presented a positive axillary status (8). In this study, the US lymph node status had the most important contribution in predicting malignancy in the nomogram, followed by suspicious calcifications on MG. Other MG features did not show distinct predictive value in this study.…”
Section: Discussionmentioning
confidence: 47%
“…Biopsy has been the recommended management approach for all 3 subcategories because of the suspicion of malignancy. However, the malignancy rate of category 4A lesions is rather low (2-10%), and the proportion of category 4A lesions was 44.5% amongst category 4-5 lesions (8). The average reported rate of BI-RADS category 4A lesions on the diagnostic US in our center is only 6.7% and is much lower for patients under 35 years old (2.7%) (8).…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…US-guided biopsy was performed using a core instrument with a 14-gauge needle or a vacuum-assisted biopsy machine with an 8-gauge needle. More than three tissue samples were obtained and placed in formalin solution and then processed for histopathology by standard procedures 13 . Patients with indefinite histological results were recommended for surgery.…”
Section: Methodsmentioning
confidence: 99%
“…A final US score (category 0–6, including subcategory 4A–4C) was assigned by the same radiologist immediately after scanning according to the second edition of BI-RADS US 9. Our radiologists assessed the US findings without referring to MG, because US and MG are usually in different departments in China and few radiologists routinely interpret both of them 14,15…”
Section: Methodsmentioning
confidence: 99%